Effect of aqueous extract of Eucalyptus Microtheca on Acanthamoeba genotype T5, an in vitro study - Frough Ashtari; Mahmoud Mahami-Oskouei; Adel Spotin; Ehsan Ahmadpour; Hadi Aali; Hamid Mahmoodpour; Mohammad Hasan Kohansal (BMC Complementary Medicine and Therapies)
Abstract Background Acanthamoeba is a resilient protozoan that causes serious diseases such as Acanthamoeba Keratitis (AK). Due to the ineffectiveness of many drugs against this parasite, plant extracts provide a promising alternative in the treatment process. This study aimed to assess the effectiveness of the aqueous extract of Eucalyptus microtheca against Acanthamoeba trophozoites and cysts in vitro. Methods In the current experimental study, Acanthamoeba isolate was cultured in a non-nutritive agar (NNA) medium. Aqueous extracts of Eucalyptus microtheca were prepared at concentrations of 10, 20, 40, and 80 mg/ mL, with exposure times of 30, 60, 90, and 120 min for trophozoites and 24, 48, and 72 h for cysts. Chlorhexidine (0.02%) and PBS served as positive and negative controls, respectively. Viability was assessed using 1% eosin dye. Results Our study revealed that the aqueous extract of Eucalyptus microtheca significantly reduced the number of both trophozoites and cysts. At 80 mg/ mL, the extract completely eliminated cysts (100%) after 24 h and reduced trophozoites by 99.33% within 120 min. Conclusion This study indicates that Eucalyptus microtheca aqueous extract possesses significant anti-Acanthamoeba properties, with effects strongly associated with concentration and exposure time (p < 0.001).